2019
DOI: 10.6061/clinics/2019/e560
|View full text |Cite
|
Sign up to set email alerts
|

Very low-calorie diet in candidates for bariatric surgery: change in body composition during rapid weight loss

Abstract: OBJECTIVE: To analyze the changes in the body composition of morbidly obese patients induced by a very low-calorie diet. METHODS: We evaluated 120 patients selected from a university hospital. Body composition was assessed before and after the diet provided during hospitalization, and changes in weight, body mass index, and neck, waist and hip circumferences were analyzed. Bioimpedance was used to obtain body fat and fat-free mass values. The data were categorized by ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 35 publications
(55 reference statements)
1
36
0
Order By: Relevance
“…Similar weight loss of between 4% and 15% has been reported in non‐bariatric surgery patients using a pre‐surgical calorie restricted diet 21, 32, 33, 38 . A high proportion of weight loss (85%) was from FM in participants receiving the VLCD intervention, likewise other studies evaluating low calorie diets on body composition showed 68.9 ‐ 85% of weight loss was from a reduction in FM without excessive loss of muscle mass 39, 40 . Using BIA to measure body composition is not without flaw, as results can be influenced by body water distribution and body morphology in individuals with obesity, potentially overestimating body FM 41 …”
Section: Discussionmentioning
confidence: 70%
“…Similar weight loss of between 4% and 15% has been reported in non‐bariatric surgery patients using a pre‐surgical calorie restricted diet 21, 32, 33, 38 . A high proportion of weight loss (85%) was from FM in participants receiving the VLCD intervention, likewise other studies evaluating low calorie diets on body composition showed 68.9 ‐ 85% of weight loss was from a reduction in FM without excessive loss of muscle mass 39, 40 . Using BIA to measure body composition is not without flaw, as results can be influenced by body water distribution and body morphology in individuals with obesity, potentially overestimating body FM 41 …”
Section: Discussionmentioning
confidence: 70%
“…Sample sizes of the studies ranged from six 51 to 259, 58 with dropout rates ranging from 0% 55 , 56 , 58 to 46% 48 at 5-year follow-up. Mean (SD) age of participants ranged from 28.5 (7.2) 50 to ≥60 years.…”
Section: Resultsmentioning
confidence: 99%
“…Mean (SD) age of participants ranged from 28.5 (7.2) 50 to ≥60 years. 56 , 58 Mean (SD) BMI of the studies ranged from 36 (5) 54 to 64.3 (2.1). 51 Obesity treatment was the primary reason for admission in eight articles, 47–51 , 53 , 56 , 57 rehabilitation for two articles, 55 , 58 and acute care for two articles, 52 , 54 (including cellulitis, 52 asthma, 52 respiratory infection, 52 cancer, 54 pancreatic disease, 54 trauma, 54 and gastrointestinal disorders 54 ) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrition prescription is an important component of nutritional interventions for weight management. In particular, calorie prescription is the key for guiding intake amounts [ 20 ]. Over time, energy intake shows an increasing trend, with values of 1500, 1700, 1800, 1900, and 2000 kcal/day at 6 months and 1, 2, 3, and 4–10 years post operation [ 9 ].…”
Section: Discussionmentioning
confidence: 99%